Channels of distribution - D.E. Visuals (Firm) (Florida : D.E. visuals, 2002)
Discusses advantages and disadvantages of direct and indirect distribution, common consumer and industrial market channels, channels in the service industries, multichannel systems, vertical marketing systems, and strategic channel decisions.
DVD format
Keywords: Marketing channels